2012
DOI: 10.1097/tp.0b013e31825c5967
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Polymorphism Ala258Ser in the Innate Receptor Gene Ficolin-2 in the Donor Predicts Improved Renal Transplant Outcome

Abstract: Presence of the ficolin-2 Ala258Ser polymorphism in the donor independently predicts improved graft outcome. Based on mechanistic data, we propose that this functional polymorphism leads to more efficient handling of injured cells by phagocytozing cells, resulting in decreased intragraft exposure to danger signals and dampened alloimmune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Ala258Ser, which represents decreased ficolin-2 concentration and increased binding capacity of ficolin-2 to GLcNAc, is associated with chronic Chagas disease (Luz et al, 2013) and leprosy . Furthermore, in renal transplantation, this SNP in the donor predicts improved outcome with lower incidence of severe rejection (Eikmans et al, 2012). In contrast, it was reported that three promoter SNPs (-986, -602, and -4) and two nonsynonymous SNPs (Thr236Met and Ala258Ser) are not associated with invasive pneumococcal disease (Chapman et al, 2007), respiratory tract infection (Ruskamp et al, 2009), or Behcet's disease (Chen et al, 2006).…”
Section: Gene Polymorphisms Serum Concentrations Of Ficolins and Thementioning
confidence: 92%
“…Ala258Ser, which represents decreased ficolin-2 concentration and increased binding capacity of ficolin-2 to GLcNAc, is associated with chronic Chagas disease (Luz et al, 2013) and leprosy . Furthermore, in renal transplantation, this SNP in the donor predicts improved outcome with lower incidence of severe rejection (Eikmans et al, 2012). In contrast, it was reported that three promoter SNPs (-986, -602, and -4) and two nonsynonymous SNPs (Thr236Met and Ala258Ser) are not associated with invasive pneumococcal disease (Chapman et al, 2007), respiratory tract infection (Ruskamp et al, 2009), or Behcet's disease (Chen et al, 2006).…”
Section: Gene Polymorphisms Serum Concentrations Of Ficolins and Thementioning
confidence: 92%
“…63 However, another study of common functional polymorphisms in the ficolin-2 gene revealed an association between this polymorphism and lower incidence of renal transplant rejection. 64 Furthermore, high pretransplant levels of ficolin-3, the most abundant ficolin in serum, showed strong association with poor allograft survival after renal transplantation. 65,66…”
Section: Role Of Ficolins In Tissue Injurymentioning
confidence: 99%
“…138 Moreover, if the donor carries this SNP, an improved outcome of renal transplantation has been reported. 139 Only a few variations in FCN3 have been detected and these are present in low frequencies. 107 A few cases of ficolin-3 deficiency have been reported to date.…”
Section: Genetic Variations and Their Association With Diseasementioning
confidence: 99%